Associations of food groups and cardiometabolic and inflammatory biomarkers: does the meal matter?. Issue 6 (24th June 2019) - Schwedhelm, Carolina; Schwingshackl, Lukas; Agogo, George O.; Sonestedt, Emily; Boeing, Heiner; Knüppel, Sven
Abstract: Increased attention has been paid to circadian patterns and how predisposition to metabolic disorders can be affected by meal timing. Currently, it is not clear which role can be attributed to the foods selected at meals. On a cross-sectional sub-cohort study (815 adults) within the European Prospective Investigation into Cancer and Nutrition-Potsdam study, we investigated whether the same foods (vegetables, fruits, refined grains, whole grains, red and processed meats) eaten at different meals (breakfast, lunch or dinner) show different associations with biomarkers of cardiometabolic risk. Meal-specific usual intakes were calculated from multiple 24-h dietary recalls. Multivariable-adjusted linear regression models showed that intake of vegetables at breakfast was associated with lower LDL-cholesterol (−0·37 mmol/l per 50 g; 95 % CI −0·61, −0·12) and vegetables at dinner was associated with higher HDL-cholesterol (0·05 mmol/l per 50 g; 95 % CI 0, 0·10). Fruit intake at breakfast was associated with lower glycated Hb (HbA1c) (−0·06 % per 50 g; 95 % CI −0·10, −0·01) and fruits at dinner with lower C-reactive protein (CRP) (−0·21 mg/l per 50 g; 95 % CI −0·42, −0·01). Red and processed meat intake at breakfast was associated with higher HbA1c (0·25 % per 50 g; 95 % CI 0·05, 0·46) and CRP (0·76 mg/l per 50 g; 95 % CI 0·15, 1·36). Our results suggest that by preferring fruits and vegetables and avoiding red and processed meats at specific meals (i.e. breakfast and dinner), cardiometabolic profiles and ultimately chronic disease risk could be improved. Lunch seemed to be a less important meal in terms of food–biomarker associations.